Groundwater governance through electricity supply management: assessing an innovative intervention in Gujarat, western India - Shah, Tushaar; Bhatt, S.; Shah, R.K.; Talati, J. (2008)
Gujarat, a rapidly industrializing state in western India, is notorious for groundwater over-exploitation. A perverse link between energy subsidies and groundwater overdraft has left the state with a bankrupt electricity utility and depleted aquifers, especially since the late 1980s. Moreover, this perverse relationship has meant that groundwater irrigators have essentially held Gujarat's non-farm rural economy to ransom. Efforts to regulate groundwater overdraft since the early 1970s have been unsuccessful, as have attempts to charge a rational electricity tariff to groundwater irrigators. During 2003-2006, drawing upon a proposal outlined by researchers, the government launched the Jyotigram (lighted village) scheme, which invested US$ 290 million to separate agricultural electricity feeders from non-agricultural ones, and established a tight regimen for farm power rationing in the countryside. By 2006, Gujarat covered almost all of its 18,000 villages under the Jyotigram scheme of rationalized power supply. With this, two major changes have occurred: (a) villages receive 24 h three-phase power supply for domestic uses, in schools, hospitals, village industries, all subject to metered tariff; (b) tubewell owners receive 8 h/day of power of full voltage and on a pre-announced schedule. The Jyotigram scheme has radically improved the quality of village life, spurred non-farm economic enterprises, halved the power subsidy to agriculture, and reduced groundwater overdraft. It has also produced positive and negative impacts on medium and large farmers, while notably harming marginal farmers and the landless, who depend for their access to irrigation on water markets which have become much smaller, post-Jyotigram. In addition, the water prices charged by tubewell owners have increased by 30-50%. We propose that the Jyotigram scheme, with some refinements, can be implemented successfully in other regions of South Asia facing similar challenges of groundwater governance.